Events, phrases, and questions - Truswell, Robert (Oxford : Oxford University Press, 2011)
Uniting work from philosophical, cognitive and linguistic perspectives, Truswell develops a model of the structure of events as perceptual and cognitive units. He predicts the acceptability of formulations, considers the individuation of events in the light of the model, and provides an account of patterns of question formation.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Includes bibliographical references and index.
Keywords: Extraction (Linguistics); Grammar, Comparative and general -- Syntax